Сoncept of the state targeted NSC KIPT program of experimental base development for basic and applied research in nuclear and high-energy physics and physics of radiation interaction with matter - Shul’ga, M.F.; Kovalenko, G.D.; Ganenko, V.B.; Levchuk, L.G.; Karpus, S.H.; Semisalov, I.L. (Вопросы атомной науки и техники, 2022)
General provisions of the Concept of development of basic and applied research at the Institute of High Energy and Nuclear Physics of the NSC KIPT are presented taking into account contemporary world trends. An analysis of the status and main research directions in Ukraine was carried out, with illuminating general problems, reasons for their occurrence and possible ways for their solution. At present, the main problem is the loss of material, technolog-ical and labor resources due to the military aggression of the Russian Federation against Ukraine. Implementation of the main provisions of the proposed concept will restore the research potential of the NSC KIPT as a leading re-search institution of the National Academy of Sciences (NAS) of Ukraine in the post-war period. Представлено загальні положення концепції розвитку фундаментально-прикладних досліджень в Інституті фізики високих енергій та ядерної фізики ННЦ ХФТІ з урахуванням сучасних світових тенденцій. Проведено аналіз стану і основних напрямків досліджень в Україні, визначено загальні проблеми, причини їх виникнення та обґрунтування шляхів їх вирішення. На даний час основною проблемою є втрати матеріально-технічних та трудових ресурсів, спричинені внаслідок військової агресії РФ проти України. Впровадження основних положень запропонованої концепції надасть можливість відновити науково-дослідний потенціал ННЦ ХФТІ як провідної науково-дослідної установи НАН України в післявоєнний період. Представлены общие положения концепции развития фундаментально-прикладных исследований в Институте физики высоких энергий и ядерной физики ННЦ ХФТИ с учетом современных мировых тенденций. Проведен анализ состояния и основных направлений исследований в Украине, определены общие проблемы, причины их возникновения и обоснования их решения. В настоящее время основной проблемой являются потери материально-технических и трудовых ресурсов вследствие военной агрессии РФ против Украины. Внедрение основных положений предлагаемой концепции позволит восстановить научно-исследовательский потенциал ННЦ ХФТИ как ведущего научно-исследовательского учреждения НАН Украины в послевоенный период.